BARK-CLOTH AND BARK-CLOTH BEATER FROM THE INDONESIAN ARCHIPELAGO - Sunarningsih, Sunarningsih (Naditira Widya, 2011)
Abstract. Archaeological remains of bark-cloths in the Indonesian Archipelago are few and leavingus only bark-cloth beaters. On the other hand, remains of bark-cloth can still be found in associationwith bark-cloth beaters in China, Taiwan, Thailand, and Malaysia. Nevertheless, a number of villagesin Indonesia are still producing bark-cloth; hence the inventory and documentation of suchethnographic data can still be carried out. Many museums in Europe collect ornamented barkcloths.Today, the productions of bark-cloths in the Indonesian Archipelago are intended as souvenirs,for instance, wall ornament. Apparently, the existence of bark-cloths in the past is closely related tothe identity of a society. Thus, this article discusses the remains of bark-cloth beaters found inIndonesia in comparison to that of in other Asian countries and their ethnographic data. Informationon bark-cloth beaters were collected from publications and archaeological research reports of BalaiArkeologi Banjarmasin (Centre for Archaeology, Banjarmasin). The outcome of the discussion wasintended to motivate further comprehensive research on bark-cloth beaters.